Reformulasi Paradigmatik Kedaulatan Sumber Daya Alam dalam Konstitusi - Safiudin. R, Achmad (Fakultas Syariah INSURI Ponorogo, 2023)
The exploitation of natural resources (SDA) and environmental destruction is not just a problem that becomes a national issue, but regional and even global. In Indonesia, natural resource wealth is understood by the government as an important capital in the implementation of national development, so the unwise use of natural resources and the environment causes these natural resources to decline both in terms of quality and quantity. This is due to the construction of the mainstream of thought of sovereignty in the constitution so far has had an impact on minimal management resulting in the utilization of natural resources without regard to the principles of justice, democracy and the sustainability of natural resources functions and is often considered not based on the ideal conservation and productivity functions. The legal issues in this paper are (a) how is the dynamics of the paradigm of natural resources sovereignty in the constitution and (b) how is the paradigmatic reformulation of natural resources sovereignty in the constitution as an effort to converge in the development of the legal system. This research is within the scope of normative law through statutory approaches, case approaches and comparative legal systems approaches. The results of the research are theoretically expected to contribute ideas and enrich the repertoire of legal science, especially environmental law related to the problem of the management paradigm towards sovereign natural resources. Practically, it is expected to be useful as input material for policymakers.